Technology Watch: Physical Activity and Hypertension - Álvarez Rojas, Andrés
This document is derived from the execution of a macro-project aimed at designing a prototype of a mobile application (app), which allows the evaluation and intervention of this population , initially, in the department of Antioquia (Colombia). The work was developed, following the predetermined phases for an effective technological surveillance, focused on patents, documents and commercial products, published in databases, specialized documents and social networks. To make an assertive query, the following keywords were used: physical activity, hypertension, cardiovascular, telehealth, app. As a result, it was evidenced that there are educational strategies that are supported by technological tools such as telephones, web pages, apps and telehealth platforms that are useful when carrying out an intervention to hypertensive patients. It is concluded that health entities are implementing digital resources for the inclusion of special populations; but at the moment, from the area of physical activity, there is not much evidence of intervention in hypertensive patients, through mobile applications.